Recent Credit Stagnation in the Mena Region : What to Expect? What Can Be Done? - Chami, Ralph (IMF Working Papers; Working Paper, 2010)
This paper examines the recent credit slowdown among Middle Eastern and North African (MENA) countries from three analytical angles. First, it finds that, similar to other regions and to its past history, a credit boom preceded the current slowdown, and that a protracted period of sluggish growth is likely going forward. Second, it uncovers a key role played by bank funding (deposit growth and external borrowing slowed considerably) but whose effect was frequently dampened by expansionary monetary policy. Third, bank-level fundamentals - capitalization and loan quality - helped to explain differences in credit growth across banks and countries.